Best practice guidelines - DEGUM recommendations on breast ultrasound, Part III/2 - special clinical indications = Best Practice Guideline - Empfehlungen der DEGUM zur Durchführung und Beurteilung der Mammasonografie, Teil III/2 - Spezielle Indikationsbereiche - Vogel-Minea, Claudia; Bader, Werner; Blohmer, Jens-Uwe; Duda, Volker; Eichler, Christian; Fallenberg, Eva; Farrokh, André; Golatta, Michael; Gruber, Ines; Hackelöer, Bernhard-Joachim; Heil, Jörg; Madjar, Helmut; et al. (Ultraschall in der Medizin, 2025)
Breast ultrasound has been established for many years as an important method in addition to mammography for clarifying breast findings. The goal of the Best Practice Guidelines Part III of the DEGUM breast ultrasound working group is to provide colleagues working in senology with information regarding the specific medical indications for breast ultrasound in addition to the current ultrasound criteria and assessment categories published in part I and the additional and optional sonographic diagnostic methods described in part II. The value of breast ultrasound for specific indications including follow-up, evaluation of breast implants, diagnostic workup of dense breast tissue, diagnostic workup during pregnancy and lactation, and the diagnostic workup of breast findings in men is discussed. Each section after the general information section contains a description of specific pathologies, followed by a short summary and DEGUM recommendations for the particular indications. The latest S3 guidelines and AGO guidelines were taken into consideration
Gesehen am 14.11.2025